NATURAL AND ARTIFICIAL INTELLIGENCE IN BONE MARROW TRANSPLANTATION AND CELL THERAPY - Duarte Barroso, Fernando; Hamerschlak, Nelson Hamerschlak (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2024)
.